Los paisajes de la frontera galaico-portuguesa - Alonso Otero, Francisco (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
Resumen: De los cerca de 1.250 kms. que delimitan la frontera hispano-portuguesa, más comúnmente conocida como “La Raya”, unos 500 kms.  forman el sector más septentrional y antiguo de todos, orientado de oeste a este, en el que se integran los límites entre Galicia y Zamora por el lado español, y de Minho y Trás-os-Montes e Alto Douro por el lado portugués. Para una mejor comprensión de los paisajes que abarca y segrega este sector septentrional de la línea fronteriza, se le ha dividido en cuatro tramos, a saber: 1) Bajo valle del Miño; 2) Entre el río Miño y el río Limia; 3) Entre el río Limia y el río Támega; y 4) Entre el río Támega y el río Duero. En este artículo se analizarán pormenorizadamente los principales rasgos paisajísticos de cada uno de ellos. Palabras clave: Raya , Galicia,  Portugal,  Paisajes,  Fortificaciones Defensivas. Abstract: The Spanish-Portuguese border, commonly known as “La Raya”, is nearly 1,250 kilometers long. Approximately 500 kilometers of this form the oldest, northern section, which runs West-East. On the Spanish side are the outer limits of Galicia and Zamora, and on the Portuguese side are the limits of Minho and Tras-os-Montes e Alto Douro. With a view to a better understanding of the landscapes lying along and forming this border, this study has been divided into four sections: 1) the Lower Miño Valley, 2) from the River Miño to the River Limia; 3) from the River Limia to the River Tamega; and 4) from the River Tamega to the River Douro. As such, the specific landscape features of these sections will be analyzed individually and in detail. Key words: Boundary line, Galicia, Portugal, Landscapes, Defensive fortifications.